Investigating the landscape of physics laboratory instruction across North America - Holmes, N. G.; Lewandowski, H. J. (Physical review. Physics education research, 2020)
Physics lab instruction is evolving in response to changing technology, a desire to better prepare students for diverse careers, and renewed focus from physics education researchers. To prepare researchers to evaluate progress in instructional labs in the future, this study set out to understand the current state of instructional physics labs in North America. Using information collected from instructors intending to use two research-based lab assessments, we evaluate the reach, organization, goals, and pedagogies from over 200 unique instructional lab courses at over 100 institutions. We find significant diversity in all aspects evaluated, with some trends in course pedagogy based on course goals and level. Namely, courses that aim to reinforce concepts, develop lab skills, or do both incorporate varied levels of agency and modeling in their instruction, with differences in first year and beyond-first year courses. We hope these analyses will be useful for instructors to situate their own courses in the national landscape and for researchers to evaluate changes in lab instruction in the future.